Bodily distalization of molars with absolute anchorage - (:unkn) unknown (My University, 2003)
Palatal implants have been used over the last two decades to eliminate headgear wear and to establish stationary anchorage. In this case report, the stability of a palatal implant for distalization of molars bodily and for anchorage maintenance was assessed. The implant was a stepped screw titanium (4.5 mm diameter x 8 mm length), and it was placed in the palatal region for orthodontic purposes. A surgical template containing a metal drill housing was prepared. Angulation of the drill housing was controlled according to the radiologic tracing of the maxilla transferred to a plaster cast section in the paramedian plane. The implant was placed using a noninvasive technique (incision, flap, and suture elimination) and left transmucosally to facilitate the surgical procedure and to reduce the number of operations. The paramedian region was selected (1) to avoid the connective tissues of the palatine suture and (2) because it is considered to be a suitable host site for implant placement. After three months of healing, the implant was osseointegrated and orthodontic treatment was initiated. For molar distalization, the Keles Slider appliance was modified and, instead of a Nance button, a palatal implant was used for anchorage. The results showed that the molars were distalized bodily at five months, and no anchorage loss was observed. At the end of the treatment, the smile was improved, and an ideal Class I molar and canine relationship, an ideal overbite, and an ideal overjet were all achieved. In conclusion, palatal implants can be used effectively for anchorage maintenance and in space-gaining procedures. Use of a three-dimensional surgical template eliminated implant placement errors, reduced chair time, minimized trauma to the tissues, and enhanced osseointegration. This method can be used effectively to achieve distalization of molars bodily without anchorage loss.
Keywords: Female; Humans; Adolescent; Esthetics, Dental; Malocclusion, Angle Class II; Tooth Movement Techniques; Titanium; Palate; Orthodontic Appliance Design; Molar; Bone Screws; Osseointegration; Smiling